Pengaruh Variasi Sudut Pengelasan Menggunakan Welding Carriage Terhadap Weld Bead Pada Pengelasan GMAW - Ilhamda, Yoga Hadi; Mutiarani, Mutiarani; Wijayanti, Ita (Jurnal Teknologi dan Riset Terapan (JATRA), 2023)
Welding using a welding carriage is carried out to get better results compared to manual welding. The purpose of this study was to determine the effect of the welding angle variation on the Weld Bead size. In this study, the welding method used is GMAW (Gas Metal Arc Welding) using S550MC steel plate material using a voltage of 30.0 V and Wire Speed 8.0 m/s. Testing is carried out using several tools to measure the results of welding (weld bead), namely welding gauge and steel crossbar. This study was conducted by comparing the results of welding (weld beads) from different welding angles, namely 45º, 60º, and 90º angles. Measurement of angular variations in this test uses an inclinometer. The comparison results are seen based on the height and width of the weld bead, while for acceptance criteria using the 1e0099 welding general requirement standard with the condition of welding width of a maximum of 13 mm and a mechanical welding height of 2 mm. Based on the test results, welding at a 90° angle variation produces a weld bead that meets the acceptance criteria. In welding using an angle of 60 ° and 45 ° produces a weld bead that does not meet the acceptance criteria. From the experimental results it was found that the smaller the welding angle the size of the weld bead became wider